Smart catalyst deposition by 3D printing for Polymer Electrolyte Membrane Fuel Cell manufacturing. (January 2021) - Cannio, Maria; Righi, Stefania; Santangelo, Paolo E.; Romagnoli, Marcello; Pedicini, Rolando; Carbone, Alessandra; Gatto, Irene
Abstract: Polymer Electrolyte Membrane Fuel Cells (PEMFC) are arguably the most employed fuel-cell types in various industry sectors, as they operate at low temperature and exhibit short start-up time and high durability. PEMFC manufacturing is currently transitioning from low-volume to mass production. Within this effort, efficient catalyst deposition to produce MEA (Membrane Electrode Assembly) electrodes has become instrumental, since very expensive raw materials are involved. This work focuses on an Additive Manufacturing (AM) technique – a modified 3D printing approach – used to release catalytic inks onto PEMFC electrodes. Some catalyst-free suspensions were designed to resemble a catalytic ink and characterized to assess their printability by microextrusion. Mixtures of distilled water, ethanol and graphite were prepared and tested. Granulometric and rheometric analyses were conducted to optimize the composition towards low viscosity values and short drying time. Repeatability of the released amount and its homogeneousness onto the target surface were evaluated. The most suitable ink formulation was loaded with platinum, a perfluorosulfonic ionomer, a pore former (NH4 CO3 ) and deposited onto Gas Diffusion Layers (GDL). Scanning Electron Microscopy (SEM) measurements were performed on the 3D-printed electrodes to characterize it. Preliminary electrochemical fuel-cell tests were carried out towards a comparison with conventional electrodes: the proposed deposition technique appears able to produce electrodes that align with state-of-the-art performance level. Graphical abstract: Image 1 Highlights: Additive Manufacturing was used to deposit catalyst inks onto PEMFC electrodes. Ink rheological behavior was defined and developed. High repeatability of the released amount ink onto the target surface was achieved. High layer homogeneousness was achieved. Electrochemical efficiency of 3D-printed electrodes was proved close to standard MEAs.